2020
DOI: 10.1007/s12178-020-09632-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Review of Automated Risk Calculators Used to Predict Postoperative Complications After Orthopedic Surgery

Abstract: Purpose of Review To discuss the automated risk calculators that have been developed and evaluated in orthopedic surgery. Recent Findings Identifying predictors of adverse outcomes following orthopedic surgery is vital in the decision-making process for surgeons and patients. Recently, automated risk calculators have been developed to quantify patient-specific preoperative risk associated with certain orthopedic procedures. Automated risk calculators may provide the orthopedic surgeon with a valuable tool for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The results of this study indicate that elderly patients with renal failure and diabetes are more likely to have postoperative complications after total hip replacement. It is Consistent with the research results of Merrill et al [ 20 ]. One possible reason is that elderly patients have more comorbidities will make them less able to withstand the stresses of anesthesia and surgery[ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study indicate that elderly patients with renal failure and diabetes are more likely to have postoperative complications after total hip replacement. It is Consistent with the research results of Merrill et al [ 20 ]. One possible reason is that elderly patients have more comorbidities will make them less able to withstand the stresses of anesthesia and surgery[ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…With the overarching goals of improving health care quality and safety, research using large data sets and predictive analytics continues to expand and evolve [ 2 , 3 , 6 , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. In particular, the field of spinal surgery has experienced an exponential increase in the development of prediction models [25] . Although more prediction models are being developed than ever before, this review confirms that only a small fraction of them undergo external validation, model updating and/or impact studies.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of this review was to evaluate whether prediction models for postoperative spine surgery complications are being adequately studied with external validation, model updating, and model impact studies. Other published systematic reviews pertaining to postoperative complications in orthopedic surgery [25] and complications or outcomes in spinal surgery [49] have been descriptive and comprehensive but have not analyzed the existing research in this manner. This review has confirmed the increase in published complication prediction models in spinal surgery, but the studies are heavily weighted towards model development and internal validation.…”
Section: Discussionmentioning
confidence: 99%
“…The ACS-NSQIP [13] was developed using a heterogeneous patient population, and by only accepting one Current Procedural Terminology (CPT) code for each risk calculation, it may have underestimated the complexity of the surgery [52,53], since many spine surgery cases comprise multiple procedures in one operation. In our model, complex spine surgery is taken into account using the modified Mirza index [29,54]. Ratliff et al [12] used the large MarketScan dataset, which included mostly younger patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%